DONETSK-DON CATACOMB CULTURE OF S.N. BRATCHENKО (Південний архів (історичні науки), 2022)
Purpose is the actualization of the concept of Donetsk-Don catacomb culture, on which S.N. Bratchenko worked in the last years of his life. Methods. The research was carried out on the basis of a historiographical synthesis, an analysis and generalization of the researcher’s works, which contained his vision of a new cultural-taxonomic unit, was carried out. Results. On the basis of many years of work with archaeological sources originating mostly from burial mounds in the south of Eastern Europe, in-depth analysis of these materials, the scientist came to the conclusion of the need to include the monuments of catacomb cultures/groups of the north-eastern area into a single formation, which he proposed to call Donetsk-Don (Don) catacomb culture. The researcher considered the basic criterion of such an association to be the similarity of the funeral rite, which was the most stable characteristic, a kind of common denominator of the new archaeological culture. Well aware of certain regional specifics of catacomb monuments in the huge area of this archaeological formation, S.N. Bratchenko singled out local groups/variants within the Donetsk-Don catacomb culture as working units, delineated for convenience by the boundaries of river basins or interfluves. Ceramic ware from burials (primarily its ornament), as well as the specific weight of certain ritual-inventory characteristics, were the criteria for differentiation. The vast majority of scientists either did not see Bratchenko’s innovation or did not understand it. The main reason for this should be recognized as the lack of a separate general work in which this concept would be explained and substantiated. Such a work by S.N. Bratchenko simply did not have time to write. Not the only one who noticed and realized the depth of the idea proposed by the classic of catacomb problems is R.O. Lytvynenko, who not only adopted a new cultural-taxonomic unit, but also repeatedly updated the new concept of S.N. Bratchenko in his works. Conclusions. The foundations of the concept of Donetsk-Don (Don) catacomb culture require further elaboration.
Keywords: Middle Bronze Age, Donetsk-Don catacomb culture, archaeological taxonomy, historiography.